Audio Effects Theory, Implementation and Application - Reiss, Joshua D. (Taylor & Francis Group, 2014)
PrefaceAbout the AuthorsAim and Scope of BookIntroduction and FundamentalsUnderstanding Sound and Digital AudioWorking with DecibelsLevel MeasurementsRepresenting and Understanding Digital SignalsRepresenting Complex NumbersFrequency and Time-Frequency RepresentationsAliasingModifying and Processing Digital SignalsThe Z Transform and Filter RepresentationDigital Filter ExampleNonlinear and Time-Varying EffectsDelay Line EffectsDelayTheoryBasic DelayDelay with FeedbackOther Delay TypesSlapback DelayMultitap DelayPing-Pong DelayImplementationBasic DelayVariationsDelay Line InterpolationCode ExampleApplicationsVibrato SimulationTheoryInterpolationImplementationLow-Frequency OscillatorParametersCode ExampleApplicationsFlangingTheoryPrinciple of OperationBasic FlangerLow-Frequency OscillatorFlanger with FeedbackStereo FlangingPropertiesCommon ParametersDepth (or Mix)Delay and Sweep WidthSpeed and WaveformFeedback (or Regeneration)Inverted Mode (or Phase)ImplementationBuffer AllocationInterpolationCode ExampleApplicationsResonant PitchesAvoiding Disappearing InstrumentsFlanging versus ChorusChorusTheoryBasic ChorusLow-Frequency OscillatorPitch-Shifting in the ChorusMultivoice ChorusStereo ChorusPropertiesCommon ParametersDepth (or Mix)Delay and Sweep WidthSpeed and WaveformNumber of VoicesOther VariationsSummary: Flanger and Chorus ComparedFilter DesignFilter Construction and TransformationSimple, Prototype Low-Pass FilterHigh-Order Prototype Low-Pass FilterChanging the Gain at the Cutoff FrequencyShifting the Cutoff FrequencyCreating a Shelving FilterInverting the Magnitude ResponseSimple Low-Pass to Band Pass TransformationPopular IIR Filter DesignLow PassHigh PassLow ShelfHigh ShelfGain at BandwidthBand Pass FiltersBand Stop FiltersPeaking and Notch FiltersThe Allpass FilterApplications of Filter FundamentalsExponential Moving Average